The mathematical model of the distribution of the research funds of the Faculty of Mathematics and Informatics - Celov, Dmitrij; Ivanauskas, Feliksas; Pikturna, Aleksas (Lietuvos matematikos rinkinys, 2002)
We evaluate the efficiency of research outputs of departments for proper distribution of research funds using a sample of MIF VU Departments’ dataset of research and publications. The tool is Data Envelopment Analysis (DEA). Research outputs, measured by points, are taken as output data. Inputs are measured by potentials of department’s personal and their salaries. The results of DEA analysis shows that some of the departments operates under increasing retum-to-scale that allows to increase overall efficiency of the departments by using additional slacks.